Pour une genèse de la compétence paysagiste - Bernadette Blanchon-Caillot (Projets de Paysage)
The research in the National landscape school in Versailles is based on an approach focused on landscape project (landscape architecture), and notably through the reconstitution of a genealogy of the landscape skills, based on the analysis of landscape realizations. It leans on a methodological axis within the description, between reading and writing, is the favourite tool and on a historical axis focused on the 1939-1975 period in France, the period of the profession’s pioneers as well as the period of the grand ensemble, a favourable hotbed to assess the notions of site and modernity. The approach aims to explicit the specific answer provided by the landscaper (at a large meaning) to urban development in order to enrich the thoughts on city and metropolis through the dimension of landscape and open spaces. After presenting the challenges, the fundamentals and the tools related to this approach, the consequences will be reviewed through examples in the fields of research, teaching, diffusion and international opportunities.